1986
DOI: 10.1177/003368828601700204
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Teaching Reduced Forms of Listening Comprehension

Abstract: This classroom research investigates the effectiveness of teaching reduced forms (e.g., "gonna" for "going to") for improving listening comprehension among EFL students in the People's Republic of China. A randomly selected experimental group (n = 16) received thirty lessons of approximately ten minutes each on reduced forms. This was part of their regular course work. At the same time a control group (n = 16) received "placebo" lessons of ten minutes on minimal pairs in pronunciation. Three measures of listen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 3 publications
2
38
0
1
Order By: Relevance
“…Results also showed that experimental participants had outperformed on "reduced forms" recognition and production tests than their peers in the control group as the result of the treatment they received during the course of study. These findings are in line with Brown and Hilferty's (1986) and Jia and fu (2011) who also confirmed the effectiveness of "reduced forms" instruction on increasing learners' "reduced forms" awareness. The results are also in line with Underwoods (2012) who also confirmed the effectiveness of "reduced forms" instruction on enhancing learners' ability of "reduced forms" production.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Results also showed that experimental participants had outperformed on "reduced forms" recognition and production tests than their peers in the control group as the result of the treatment they received during the course of study. These findings are in line with Brown and Hilferty's (1986) and Jia and fu (2011) who also confirmed the effectiveness of "reduced forms" instruction on increasing learners' "reduced forms" awareness. The results are also in line with Underwoods (2012) who also confirmed the effectiveness of "reduced forms" instruction on enhancing learners' ability of "reduced forms" production.…”
Section: Resultssupporting
confidence: 88%
“…The term "reduced forms" is taken from Brown and Hilferty (1986) and refers to the phenomenon of phonological simplification and variation commonly observed in the informal speech of native speakers. According to Cele-Murica, Brinton, and Goodwin (1996) "reduced forms" involve unstressed vowels, omitted sounds, and other alternation of the full form".…”
Section: "Reduced Forms"mentioning
confidence: 99%
“…Reduced forms are defined as the ''phonological simplifications or variations'' (Ito, 2001) and depict ''the spontaneous pronunciation changes in adjacent words or sounds spoken at a natural speed'' (Bowen, 1975). Collectively, reduced forms designate ''the processes of contraction, elision, assimilation, and reduction'' (Brown & Hilferty, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Brown & Hilferty (1986) suggest that there is a correlation between the frequency and variety of ESL students' contractions and their proficiency in ESL. A study (Brown, 1986) of the language of six ESL students provides data that indicate that 1) contraction frequency correlates with general proficiency in English as…”
Section: Listening Instructionmentioning
confidence: 99%
“…It is believed that providing greater preparation time in pre-task planning stage on a tape-based oral test will reduce stress and the perceived difficulty level. Brown (1986) reported other difficulty factors including inadequate response time, unfamiliar vocabulary, speed of voices on the tape, lack of clarity in instructions, unclear prompts, too much input material to process and lack of familiarity with the task type. Whereas tasks features that lead to more difficulty level can be revised, the control for the attributes of the candidate is difficult.…”
Section: Introductionmentioning
confidence: 99%